Cavernous carotid venous artery aneurysm: a rare complication of head injuries - Larghero Ibarz, Pedro; Rodríguez Barrios, R; Scherchener, J; Morquio, A. (Cirugía del Uruguay, 2020)
Presented at session 12th November 1947